Copyright and the information society in Euope : a matter of aiming as well as content. - BENTLEY, Lionel (1997)
Examines the response of the European Commission to various technologica changes, in particular digitization, which may impact on the creation and distribution of texts and other cultural works. Cautions the European Commission not to respond too hastily to these changes in the environment within which copyright law operates.